2016
DOI: 10.1186/s12890-016-0266-5
|View full text |Cite
|
Sign up to set email alerts
|

Abediterol, a novel long-acting β2-agonist: bronchodilation, safety, tolerability and pharmacokinetic results from a single-dose, dose-ranging, active-comparator study in patients with COPD

Abstract: BackgroundAbediterol is a novel, once-daily long-acting β2-agonist in development for the treatment of chronic obstructive pulmonary disease (COPD) and asthma in combination with an anti-inflammatory agent. This Phase IIa, randomised, double-blind, crossover study investigated the bronchodilation, safety, tolerability and pharmacokinetics of abediterol in patients with moderate to severe COPD.MethodsSeventy patients (aged ≥40 years, Global initiative for chronic Obstructive Lung Disease Stage II/III) were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
(25 reference statements)
0
10
0
1
Order By: Relevance
“…Later dose-ranging studies of abediterol in patients with stable asthma (dose range 0.313-2.5 lg (Singh et al 2014)) and in patients with stable COPD (dose range 0.625-10 lg (Beier et al 2016) once daily) have demonstrated clinically and statistically significant dose-related improvements in bronchodilation compared with placebo. The lack of dose-response in bronchodilatory effect in this study suggests that the doses tested were at the top of the dose-response curve.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Later dose-ranging studies of abediterol in patients with stable asthma (dose range 0.313-2.5 lg (Singh et al 2014)) and in patients with stable COPD (dose range 0.625-10 lg (Beier et al 2016) once daily) have demonstrated clinically and statistically significant dose-related improvements in bronchodilation compared with placebo. The lack of dose-response in bronchodilatory effect in this study suggests that the doses tested were at the top of the dose-response curve.…”
Section: Discussionmentioning
confidence: 99%
“…; Beier et al. ). In patients with mild‐to‐moderate asthma, abediterol (5–25 μ g) demonstrated significant improvements in lung function compared with placebo and salmeterol 50 μ g twice daily as early as 5 min postdose, with a safety and tolerability profile consistent with that expected for a β 2 ‐agonist (Beier et al.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Все дозы абедитерола хорошо переносились. Также у 70 больных с ХОБЛ со стадиями GOLD 2-3 все дозы абедитерола (0,625-10 мкг) обеспечивали клинически и статистически значимую, зависимую от дозы бронходилатацию в сравнении с плацебо и хорошо переносились [51]. Интересно, что абедите-рол в дозах 2,5, 5 и 10 мкг приводил к достоверному улучшению по сравнению с индакатеролом.…”
Section: обзорыunclassified
“…All doses of abediterol were well tolerated. Also in 70 COPD patients who were GOLD stage 2/3, all doses of abediterol (0.625-10 μg) provided clinically and statistically significant, dose-dependent improvements in bronchodilation versus placebo, and were well tolerated [51]. Interestingly abediterol 2.5, 5 and 10 μg gave significant improvements versus indacaterol.…”
mentioning
confidence: 92%